Anti‐ and Pro‐Nociceptive mechanisms in neuropathic pain after human spinal cord injury. (10th September 2022) - Lütolf, Robin; De Schoenmacker, Iara; Rosner, Jan; Sirucek, Laura; Schweinhardt, Petra; Curt, Armin; Hubli, Michèle
Abstract: Background: Deficient endogenous pain modulation and increased nociceptive excitability are key features of central sensitization and can be assessed in humans by conditioned pain modulation (CPM, anti‐nociceptive) and temporal summation of pain (TSP, pro‐nociceptive), respectively. This study aimed to investigate these measures as proxies for central sensitization in subjects with chronic neuropathic pain (NP) after spinal cord injury (SCI). Methods: In paraplegic subjects with NP (SCI‐NP; n = 17) and healthy controls (HC; n = 17), parallel and sequential sham‐controlled CPM paradigms were performed using pressure pain threshold at the hand, that is, above lesion level, as test stimulus. The conditioning stimulus was a noxious cold (verum) or lukewarm water bath (sham) applied contralaterally. Regarding pro‐nociceptive mechanisms, a TSP protocol with individually‐adjusted pressure pain stimuli at the thenar eminence was used. CPM and TSP magnitudes were related to intensity and spatial extent of spontaneous NP. Results: Neither the parallel nor sequential sham‐controlled CPM paradigm showed any significant inhibition of above‐level pressure pain thresholds for SCI‐NP or HC. Accordingly, no group difference in CPM capacity was found, however, subjects with more intense spontaneous NP showed lower inhibitory CPM capacity. TSP was observed for both groups but was not enhanced in SCI‐NP. Conclusions: Our results do not support altered above‐level anti‐ or pro‐nociceptive mechanisms in SCI‐NP compared with HC; however, they also highlight the relevance of spontaneous NP intensity with regards to the capacity of endogenous pain modulation in SCI subjects. Significance: Central sensitization encompasses deficient endogenous pain modulation and increased nociceptive excitability. These two mechanisms can be assessed in humans by conditioned pain modulation and temporal summation of pain, respectively. Our data demonstrates a lack of descending pain inhibition only in subjects with severe neuropathic pain which may hint towards central sensitization at spinal and/or supra‐spinal levels. Disentangling the mechanisms of endogenous pain modulation and neuronal hyperexcitability might improve mechanism‐based treatment of neuropathic pain in subjects with spinal cord injury.